The Effect of Liquidity, Solvency and Profitability on Dividend in the Manufacturing Listed Firms on the Indonesian Stock Exchange - Djazuli, Abid; Dodi, Dodi (International Journal of Finance Research, 2020)
This study aims to investigate the effect of liquidity, solvency and profitability on dividend in the manufacturing listed firms on the Indonesian Stock Exchange for the period of 2010 to 2018. The variables employed in this study are liquidity, solvency, profitability and dividend per share. The Ordinary Least Square (OLS) regression is used to analyze the data. The data is collected from the Indonesian Stock Exchange (IDX) website. The results reveal that liquidity, solvency and profitability have a significant effect on Dividend Per Share of Manufacturing Companies on the Indonesia Stock Exchange. Current Ratio, Cash Ratio, Debt to Equity Ratio, Debt to Asset Ratio, Net Profit Margin, and Earning per Share have a positive and significant effect on Dividend per Share. Therefore, manufacturing companies listed on the Indonesia Stock Exchange must maintain stability, liquidity, solvency and profitability in order to increase Dividend per Share.